Penerapan Aplikasi Microsoft Excel Dalam Pengelolaan Data Nilai Siswa Pada TK Kartika I-1 Medan Helvetia - Wulan Dari; Siti Aliyah; Rikha Ira Setiyawati (Fakultas Teknik Universitas Cenderawasih, 2023)
The application of student data management training aims to provide participants with understanding and skills in using Microsoft Excel for student data management. Management of student data is often needed in data management, such as making student report cards every semester at school. The Microsoft Excel application allows for personal and efficient management, by combining data from separate sources into one excel. During the training, participants will be taught the introductory concept of Microsoft Excel, the steps for preparing data, creating value columns in Excel, and merging data into templates. This training will also discuss the benefits of using Microsoft Excel, including time efficiency and accuracy in managing student data to be processed. Through a combination of theory and practical exercises, participants expected to be able to master the steps in the process of managing student data which will be explained using Microsoft Excel. It is hoped that the results of this training will give participants the ability to create personal and efficient student value data, including education and other organizations. Thus, this training contributes to increasing the effectiveness of communication in various activities that involve the process of managing student value data.